2005
DOI: 10.1079/phn2004666
|View full text |Cite
|
Sign up to set email alerts
|

Consumer understanding and use of nutrition labelling: a systematic review

Abstract: Objective: To explore published and unpublished research into consumer understanding and use of nutrition labelling which is culturally applicable in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
559
3
29

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(631 citation statements)
references
References 18 publications
40
559
3
29
Order By: Relevance
“…Nevertheless, 62 % of the study population reported being familiar with the logo, more so among women and more highly educated participants. This is in line with results from earlier studies investigating nutrition logos (9,(25)(26)(27)(28)(29) .…”
Section: Familiarity and Logo Usesupporting
confidence: 92%
“…Nevertheless, 62 % of the study population reported being familiar with the logo, more so among women and more highly educated participants. This is in line with results from earlier studies investigating nutrition logos (9,(25)(26)(27)(28)(29) .…”
Section: Familiarity and Logo Usesupporting
confidence: 92%
“…This reiterates the observation that quantitative techniques, especially questionnaire surveys to elicit information, often provide little information on whether the respondents actually behave in the way claimed (11,31) ; hence the use of qualitative techniques like FGD has distinct methodological advantages.…”
Section: Discussionmentioning
confidence: 77%
“…Children, adolescents, obese older adults, individuals with less education and/or nutrition knowledge, people with lower disposable income and those with lower health awareness are less likely to use labels and/or effectively process the nutrition information presented (30)(31)(32) . Moreover, whether consumers can understand and use nutrition facts labels is contingent upon the purpose of the task (5)(6)(7)(8) . A majority appears capable to retrieve basic facts and make simple calculations/comparisons between products using numerical information on the label, but their ability and accuracy decline as the complexity of the task increases.…”
Section: Discussionmentioning
confidence: 99%
“…A long line of research documents consumers' understanding and use of nutrition facts labels, as well as their impact on dietary behaviour (5)(6)(7)(8) . A substantial proportion of US consumers report regular use of nutrition facts labels to guide their selection of food products (5)(6)(7)(8) .…”
mentioning
confidence: 99%
See 1 more Smart Citation